Pengaruh Background factor Terhadap Pembentukan Niat Berwirausaha: Theory Planned Behavior - Saragih, Fernando (Jurnal Bisnis dan Kewirausahaan, 2023)
Economic growth is an achievement that must be considered in various regions, where one of the inhibiting factors is the unemployment rate. The high level of unemployment is a problem faced by various regions, including in NTT, precisely in the City of Kupang. The magnitude of the problem and the impact of unemployment is one of the urgency of research, where increasing entrepreneurial intentions is the right solution. This solution is based on Theory of Planned Behavior. This theory is based on Background factors which focus on 3 factors. These three factors are studied using a quantitative approach to the survey method. The data obtained by using a questionnaire (valid and reliable). The sample consisted of 82 respondents. Then the data (fulfilling the classical assumptions) were analyzed using SPSS with multiple linear regression analysis. Based on this analysis, the results show that income expectations and personality have a positive and significant effect, while social media has a negative and significant effect. Based on these results, researchers emphasize the importance of income expectations in encouraging entrepreneurial intentions. In addition, this study emphasizes personality as the dominant factor. Finally, the researcher emphasizes evaluating the use of social media (have fun).